The magnitude and frequency of storm surge in southern New Zealand. Issue 2 (3rd April 2021) - Adam, Ryan J.; Hilton, Michael J.; Jowett, Tim; Stephenson, Wayne J.
ABSTRACT: There is currently little understanding regarding storm surge in New Zealand, particularly in the southern region. To date, there has been no attempt to establish the frequency and magnitude of storm surge using observed sea level data on the open coast. The aim of this study is to examine the nature of storm surge in southern New Zealand and explore the influence of the Southern Annular Mode (SAM) and the El Nino Southern Oscillation (ENSO) on the frequency and magnitude of storm surge. Bayesian estimation is used through the 'extRemes' package in R to determine the return period for storm surge at three locations around southern New Zealand. The 100-year return level varied between 0.91 and 1.31 m. In addition, a statistically significant increase (2.88%) in storm surge intensity (SSI) on the south-east coastline was found. Applying cross-correlation to assess the response of SSI to ENSO and SAM, returned no detectable relationship, except a weak relationship between SAM and SSI on the south-east coast where a two-three month lagged response was present.